2005
DOI: 10.1080/09674845.2005.11732698
|View full text |Cite
|
Sign up to set email alerts
|

Role of Momordica charantia in maintaining the normal levels of lipids and glucose in diabetic rats fed a high-fat and low-carbohydrate diet

Abstract: This study aims to assess whether or not a methanol extract of Momordica charantia is able to normalise lipid and glucose levels in diabetic rats fed a high-fat and a low-carbohydrate diet. Different doses of the extract are administered orally for 45 days. The rats are bled at the beginning of the experiment and at 15-day intervals. Blood glucose, triglyceride, low-density lipoprotein (LDL), high-density lipoprotein (HDL) and cholesterol are estimated. Results showed that M. charantia extract normalised blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 7 publications
4
15
0
Order By: Relevance
“…Correspondence among perceived healthiness, number of medicinal claims, and perceived taste of the recorded South-Asian vegetables: ( ) vegetables whose taste is perceived as "soft, bland, sweet"; ( ) vegetables whose taste is perceived as bitter; (᭹) vegetables whose taste is perceived as aromatic ("like aniseeds"). Plant codes are reported in Table 2. many bio-scientific studies conducted during the last decade have confirmed them (Grover and Yadav, 2004;Chaturvedi, 2005).…”
Section: Traditional Strategies To Manage Diabetesmentioning
confidence: 79%
“…Correspondence among perceived healthiness, number of medicinal claims, and perceived taste of the recorded South-Asian vegetables: ( ) vegetables whose taste is perceived as "soft, bland, sweet"; ( ) vegetables whose taste is perceived as bitter; (᭹) vegetables whose taste is perceived as aromatic ("like aniseeds"). Plant codes are reported in Table 2. many bio-scientific studies conducted during the last decade have confirmed them (Grover and Yadav, 2004;Chaturvedi, 2005).…”
Section: Traditional Strategies To Manage Diabetesmentioning
confidence: 79%
“…We and others have demonstrated that besides improving glucose and lipid metabolism [26,30-32], BMJ is also effective in improving hyperlipidemia in diabetic and obese rodents as well as reduces body weights in mice fed high-fat diet [24,25,33]. However, the effects of bitter melon on human adipocytes have not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Bitter melon is a traditional plant used by ayurvedic doctors of medicines to benefit various conditions including diabetes [2]. The effect of bitter melon on various diabetes associated cardiovascular risk factors like plasma lipids, obesity and insulin resistance is known [3,4] and the present study is designed to determine the effect of bitter melon on a recently investigated cardiovascular (CV) risk marker/factor, sialic acid. Sialic acid is used to be a group name for acetylated derivatives of neuraminic acid and the serum level of it is increased in type2 diabetes mellitus [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%